Management of Pain in Children with Burns - M. Gandhi; C. Thomson; D. Lord; S. Enoch (International Journal of Pediatrics)
Burn injuries are common in children under 10 years of age. Thermal injury is the most common mechanism of injury and scalds account for >60% of such injuries. All children with burns will experience pain, regardless of the cause, size, or burn depth. Undertreated pain can result in noncompliance with treatment and, consequently, prolonged healing. It is acknowledged that the monitoring and reporting of pain in children with burns has generally been poor. Due to the adverse physiological and emotional effects secondary to pain, adequate pain control is an integral and requisite component in the management of children with burns. A multidisciplinary approach is frequently necessary to achieve a robust pain relief. Key to successful treatment is the continuous and accurate assessment of pain and the response to therapy. This clinical review article discusses the essential aspects of the pathophysiology of burns in children provides an overview of pain assessment, the salient principles in managing pain, and the essential pharmacodynamics of commonly used drugs in children with burn injuries. Both pharmacological and nonpharmacological treatment options are discussed, although a detailed review of the latter is beyond the scope and remit of this article.